A Parallel Numerical Method for Risk Assessment of Myocardial Infarction During Liver Transplantation: A Case Study (Advances in Applied Mathematics and Mechanics, 2022)
Coronary artery disease is a devastating complication of some patients undergoing liver transplantation. Anesthesia, anhepatic blood flow occlusion, and reperfusion of the liver can cause severe fluctuations in hemodynamics. However, thevast majority of liver transplant patients cannot undergo invasive coronary examinations due to their critical illness and abnormal coagulation function. In this paper,we present a retrospective case of acute myocardial infarction during surgery in orderto demonstrate a noninvasive method to obtain coronary hemodynamic functional information based on scalable computational fluid dynamics technology. A $P_1−P_1$ stabilized finite element method and second-order backward differentiation formula areapplied to discretize the time-dependent Navier-Stokes equations in the spatial andtemporal directions, respectively. A Windkessel model constructed based on the measured clinic data is used to characterize the outlet blood flow. We then apply a parallelNewton-Krylov method with a restricted additive Schwarz preconditioner to accelerate the timeliness of the simulation. The simulated functional indicator successfullyverifies the myocardial ischemia in the anhepatic phase of liver transplantation. Wealso present the parallel performance of the algorithm on a supercomputer, and theresults show that the proposed solver achieves over 55% parallel efficiency with 3840processor cores.